The Common Foundations of Principles of Jurisprudence and Classical Hermeneutics in Text Comprehension - Ã˜Â¢Ã˜Â²Ã˜Â§Ã˜Â¯, Ã˜Â¹Ã™Â„Ã›ÂŒÃ˜Â±Ã˜Â¶Ã˜Â§; Ã˜Â¢Ã˜Â²Ã˜Â§Ã˜Â¯, Ã˜ÂªÃšÂ©Ã˜ÂªÃ™Â…; Ã™Â„Ã˜Â¹Ã™Â„ Ã˜Â±Ã™ÂˆÃ˜Â´Ã™Â†, Ã™ÂÃ˜Â§Ã˜Â·Ã™Â…Ã™Â‡ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
One of the important issues in the humanities in general and in religious studies in particular is the comprehension of the meaning of the text. Dealing with the theoretical bases of interpretation and comprehension of the text, hermeneutics is a branch of the humanities which fully serves this objective. The same objective is likewise followed in the study of the principles of jurisprudence (usÅ«l-i fiqh) whose function is the inference of religious precepts from the existing religious texts and resources. Dealing with the words and terms in these resources, the scholars of principles of jurisprudence are thus obliged to discover the rules for text comprehension. Concerning the common grounds shared between hermeneutics and the principles of jurisprudence, the conduction of a comparative study seems necessary for the better understanding of definite principles and standards of text comprehension in light of the common foundations of the two disciplines. Since among all branches of hermeneutics the classical hermeneutics has the closest affinity to principles of jurisprudence, the present descriptive analytical study, applying library data and textual references, investigates the common foundations shared between the two disciplines of classical hermeneutics and principles of jurisprudence and describes the following six common foundations: 1.The centrality of the author 2.Normalism 3.Objectivism and meaning determination 4.The possibility of surpassing the historical obstacles of comprehension (the principle of non-transference of meaning) (isÄlat-i âadam-i naql) 5.Following the common rules of comprehension 6.prevention of the influence of the presuppositions.